Metabolic regulation of insulin secretion in health and disease. (12th April 2021) - Haythorne, Elizabeth; Ashcroft, Frances M
Abstract : Despite the current media focus, Covid-19 is not the only current pandemic. There is also a global pandemic of diabetes. It is caused by an insufficiency of the hormone insulin, which lowers blood glucose levels. Here we highlight recent work that addresses the question of how insulin is normally secreted from the β-cells of the pancreas and what goes wrong with this process in diabetes. We focus on the metabolic regulation of the ATP-sensitive potassium channel, an ATP-gated membrane pore that regulates insulin secretion. We show that when this pore is shut, insulin is released, and when it is open, insulin release is prevented. As may be expected, genetic mutations that impair the ability of ATP to close the channel cause neonatal diabetes. We also consider if a failure of β-cell metabolism to generate enough ATP to close the channel may lead to the progressive decline in β-cell function in type 2 diabetes.